LEARNING TO NOTICE: PROFESSIONAL VISION AND CHALLENGING BEHAVIOUR IN THE CLASSROOM - Sokolová, Lenka (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Based on the Talis study teachers spend about 13% of their teaching time keeping order in the classroom and solving disciplinary problems. Especially student and novice teachers often report tension and anxiety related to the misbehaviour, disruptive behaviour, and challenging classroom situations. When teachers need to cope with a challenging incident in the classroom they usually go through a three-phase process comprising a) identification of a situation (selective attention), b) interpretation of a scene (using either knowledge-based reasoning or implicit, intuitive interpretation) and c) intervention (taking action). This study aims to investigate the development of professional vision related to challenging situations in the classroom among student teachers. 40 junior (bachelor) and 40 senior (master) student teachers were watching a classroom video with the example of disruptive behaviour. Then they wrote short scripts describing the situation. Their answers were analysed in the context of identification, interpretation and intervention model. Both qualitative and quantitative differences were found between the groups. Implications for further research and teacher training are discussed.